Dynamic deformation behaviors and constitutive relations of an AlCoCr1.5Fe1.5NiTi0.5 high-entropy alloy. (15th July 2017) - Zhang, T.W.; Jiao, Z.M.; Wang, Z.H.; Qiao, J.W.
Abstract: A new high-entropy alloy, AlCoCr1.5 Fe1.5 NiTi0.5, with dual-phase body-centered cubic structure, exhibits excellent compression strength and large plasticity upon quasi-static and dynamic loadings. Positive strain-rate sensitivity on the yielding strength is available, and the work-hardening behavior weakens with increasing the strain rates due to the adiabatic heating effect upon dynamic loadings. Considering the adiabatic temperature rise converted by plastic deformation work at high strain rates, the flow behavior is characterized by employing the modified Johnson-Cook model. Graphical abstract: